NADPH oxidase 4 expression in the normal endometrium and in endometrial cancer - Christine Degasper; Andrea Brunner; Natalie Sampson; Irina Tsibulak; Verena Wieser; Hannah Welponer; Christian Marth; Heidi Fiegl; Alain Gustave Zeimet (Tumor Biology)
The aim of this study was to explore the role of NOX4 in the biology of the normal endometrium and endometrial cancer. NOX4 plays a key role in other adenocarcinomas and has been implicated in the pathogenesis of diabetes and obesity, which are important risk factors for endometrial cancer. NOX4 expression was assessed in 239 endometrial cancer and 25 normal endometrium samples by quantitative real-time polymerase chain reaction, in situ hybridization, and immunohistochemistry. DNA methylation of the NOX4 promoter was determined by means of MethyLight PCR. Data were correlated with clinicopathological parameters and analyzed in the context of diabetes and body mass index. In the normal endometrium, NOX4 microRNA expression was significantly higher in the secretory transformed compared with proliferative endometrium ( p  = 0.008). In endometrial cancer specimens, NOX4 expression did not differ between diabetic and non-diabetic patients, but was the highest in patients with a body mass index ≤ 26 ( p  = 0.037). The lowest NOX4 expression was found in carcinosarcomas ( p  = 0.007). High NOX4 expression predicted poorer clinical outcome with regard to overall survival, especially in non-diabetic patients and those with a body mass index > 20. Independent prognostic significance of NOX4 transcripts was retained in type I endometrial cancer and was the most meaningful in patients with a body mass index > 20. No prognostic impact was shown for NOX4 promoter methylation in endometrial cancer. For the first time, we demonstrate that NOX4 plays a considerable role in the cycle-dependent changes in the normal endometrium and in the biology of endometrial cancer.